Use of Video and Robot Simulation at MIN 1 Kepahiang Bengkulu - Afizal Mayub; Rendy Wikrama Wardana; Henny Johan (CV Media Inti Teknologi, 2022)
Community service activities are one of the university's tridharma activities that must be carried out by every lecturer, therefore lecturers of the Bengkulu University Master of Science Program in collaboration with teachers of Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu on March 31, 2022 have carried out Community Service activities at Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu. This collaboration is in the form of community service activities at Madrasah Ibtidaiyah Negeri 1 Kepahiang, Bengkulu with the title